2014
DOI: 10.4103/2249-4863.130278
|View full text |Cite
|
Sign up to set email alerts
|

Preventing coronary heart disease risk of slum dwelling residents in India

Abstract: Coronary heart disease (CHD) is the top cause of mortality and morbidity in India. People in slums are generally at a higher risk for CHD than Indians living in more affluent areas mostly because of the higher prevalence of major CHD risk factors such as uncontrolled hypertension and tobacco use amongst them. Knowing their CHD risk perceptions and bringing them into line with the actual CHD risk is a prerequisite for effective CHD risk management. Consequently, there is need to develop tailored interventions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…19 There are several risk factors commonly present in hypertensive patients, but they often remain asymptomatic. 20 In accordance with this, it was observed in our survey that majority of physicians tend to calculate CV risk in only 30%-50% of their hypertensive patients without comorbidities. This highlights the fact that a vast majority of the patient population may remain undetected of their CV risk, which adds to the burden of CV mortality, and hence timely assessment is crucial for hypertension and CV risk reduction.…”
Section: Discussionsupporting
confidence: 82%
“…19 There are several risk factors commonly present in hypertensive patients, but they often remain asymptomatic. 20 In accordance with this, it was observed in our survey that majority of physicians tend to calculate CV risk in only 30%-50% of their hypertensive patients without comorbidities. This highlights the fact that a vast majority of the patient population may remain undetected of their CV risk, which adds to the burden of CV mortality, and hence timely assessment is crucial for hypertension and CV risk reduction.…”
Section: Discussionsupporting
confidence: 82%
“…In the research done by Dhar L this has been found to be true. 27 Work done by Kunungo et al has shown that there is a statistically significant association between early deaths due to coronary heart disease and uncontrolled hypertension. 28 Even though a strong association has been found by various authors regarding uncontrolled hypertension and risk factors like level of education, regularity of treatment, frequency of check-up, salt intake, Body Mass Index and waist to hip ratio, we failed to discover a statistically significant relationship by our study.…”
Section: Discussionmentioning
confidence: 99%
“…27 Cardiovascular diseases could be attributed to the higher presence of CVD related risk factors such as uncontrolled hypertension and tobacco use which is common among urban slum dwellers. 28 The high prevalence of respiratory and gastrointestinal disorders could be attributed to poor living conditions, water, overcrowding, smoking and exposure to household smoke. 29 The high prevalence of CVD in Mumbai and gastrointestinal diseases in Pune could be as a result of local factors like increased air pollution, smoking and alcohol consumption, unavailability of clean drinking water and inadequate sanitation.…”
Section: Discussionmentioning
confidence: 99%